Consumption Habits and Cinema Attendance of Media Communication University Students - Marcos Ramos, María; Martín García, Teresa; Higueras Ruiz, María José; García Alonso, Elena María (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2026)
The objective of this study is to determine the consumption habits and cinema attendance of Audiovisual Communication university students. An online survey was carried out with the participation of 92 students belonging to the Degree at the University of Salamanca. The results indicated that students continue to go to the cinema, especially in higher grades, for the social factor and the added value. The price or the streaming platforms did not affect their attendance. However, a more significant relationship was found with regard to video games. This preliminary study shows interesting characteristics about the leisure, cinema attendance, or cinema tastes.